Theology After Deleuze - Justaert, Kristien (Deleuze Encounters., 2012)
Deleuze's relationship with theology is a complex one. Indeed, there seem to be manypossible objections to such an 'assemblage' taking place. In the first book ofits kind to engage with this seemingly problematic dialogue, Kristien Justaertshows the ways in which Deleuze's thought can in fact advance issues inpolitical and liberation theology in particular, while also exploring theimportant theological and spiritual aspirations contained in Deleuze'sphilosophy itself, as part of his lifelong quest for the 'Absolute'. Justaert examines the theological components in Deleuze's writings, investiga.